Pelatihan Dasar Coding Menggunakan Media Pembelajaran Berbasis Coding Block pada Siswa SD Kelas VI : Studi Kasus: Yayasan Kemala Bhayangkari 1 Medan - Indra Syah Putra; Feri Ranja; Fatimah Qadarsih (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of digital technology highlights the importance of introducing computational thinking skills from an early age, including at the elementary school level. One effective approach to introducing basic programming concepts is through block-based coding learning media that are visual, interactive, and engaging. This community service activity aimed to improve elementary school students’ understanding and interest in basic coding through hands-on training using block-based coding media. The program was implemented with sixth-grade students at Yayasan Kemala Bhayangkari 1 Medan. The activity employed a hands-on training approach consisting of several stages, including an introduction to basic coding concepts, familiarization with the Blockly Games interface, and practical exercises involving puzzle and maze challenges designed to develop logical thinking, sequencing, and problem-solving skills. The evaluation was conducted through direct observation of student participation and assessment of students’ ability to complete the given challenges. The results demonstrated that the use of Blockly Games effectively increased students’ enthusiasm, active engagement, and understanding of basic programming logic. Students who initially perceived programming as difficult showed greater interest and confidence due to the colorful, visual block-based instructions that were easy to understand and enjoyable. This community service activity is expected to serve as an effective introductory model for coding education and to support the development of digital literacy among elementary school students.